Cultures of inquiry from epistemology to discourse in sociohistorical research - Hall, John R. 1946- (Cambridge Univ. Press, 1999)
Cultures of Inquiry provides a unique overview of research methodologies in social science, historical and cultural studies.
Keywords: Analyse du discours; Cultuur; Histoire sociale - Méthodologie; Information sociale; Sciences sociales - Méthodologie; Sociaal-wetenschappelijk onderzoek; Social history - Methodology; Social sciences - Methodology; Sociale geschiedenis (wetenschap); Épistémologie sociale; Kultur; Sozialgeschichte; Sozialwissenschaften; Historical sociology -- Methodology; Historical sociology -- Research -- Methodology; Knowledge, Sociology of; Methodologie; Kulturwissenschaften; Geschichtswissenschaft; Methode